Integrating biochemical and anatomical characterizations with transcriptome analysis to dissect superior stem strength of ZS11 (Brassica napus) - Tian, Zhengshu; Wang, Xinfa; Dun, Xiaoling; Tian, Ze; Zhang, Xiaoxue; Li, Jinfeng; Ren, Lijun; Tu, Jinxing; Wang, Hanzhong (Frontiers in Plant Science, 2023)
Stem lodging resistance is a serious problem impairing crop yield and quality. ZS11 is an adaptable and stable yielding rapeseed variety with excellent resistance to lodging. However, the mechanism regulating lodging resistance in ZS11 remains unclear. Here, we observed that high stem mechanical strength is the main factor determining the superior lodging resistance of ZS11 through a comparative biology study. Compared with 4D122, ZS11 has higher rind penetrometer resistance (RPR) and stem breaking strength (SBS) at flowering and silique stages. Anatomical analysis shows that ZS11 exhibits thicker xylem layers and denser interfascicular fibrocytes. Analysis of cell wall components suggests that ZS11 possessed more lignin and cellulose during stem secondary development. By comparative transcriptome analysis, we reveal a relatively higher expression of genes required for S-adenosylmethionine (SAM) synthesis, and several key genes (4-COUMATATE-CoA LIGASE, CINNAMOYL-CoA REDUCTASE, CAFFEATE O-METHYLTRANSFERASE, PEROXIDASE) involved in lignin synthesis pathway in ZS11, which support an enhanced lignin biosynthesis ability in the ZS11 stem. Moreover, the difference in cellulose may relate to the significant enrichment of DEGs associated with microtubule-related process and cytoskeleton organization at the flowering stage. Protein interaction network analysis indicate that the preferential expression of several genes, such as LONESOME HIGHWAY (LHW), DNA BINDING WITH ONE FINGERS (DOFs), WUSCHEL HOMEOBOX RELATED 4 (WOX4), are related to vascular development and contribute to denser and thicker lignified cell layers in ZS11. Taken together, our results provide insights into the physiological and molecular regulatory basis for the formation of stem lodging resistance in ZS11, which will greatly promote the application of this superior trait in rapeseed breeding.